La sculpture de l’Antiquité tardive et du haut Moyen Âge en péninsule Ibérique, une révision nécessaire - Gisela Ripoll (École du Louvre, 2021)
Late Antique and Early Medieval sculpture in the Iberian Peninsula does not have a complete corpus, but a large number of dispersed studies that allow us to establish a state of the art. We have corpora for regions, cities or museum collections, such as Badajoz, Córdoba, Tarragona or Toledo, as well as thematic directories, such as figurative sculpture, liturgical altars or funerary sculpture. However, specific studies on the prestige spolia concerning sculpture and epigraphy are lacking, distinguishing them from material of an exclusively constructive nature, as well as good analyses of liturgical furniture, local workshops, imports and a good chronological sequence of productions. The objective of this presentation is to offer a state of knowledge on this material, on iconography and production, in order to identify future work mechanisms, especially archaeometric analysis.